Aquaculture as a source of functional food - A. V. Zhigin; M. V. Sytova; Yu. I. Yesavkin (Известия ТИНРО)
Current state of functional nutrition is analyzed. Principles and methods for production of the natural and artificially enriched functional food of animal origin in Russia and other countries are overviewed. Possibility of using the fish reared at fish farms as a raw material for functional nutrition is shown. Experience of such raw materials production in aquaculture is still insufficient, in particular for the in vivo enrichment. High-quality raw materials for the functional nutrition can be produced in aquaculture with recirculated water system. Meat of rainbow trout (Oncorhynchus mikiss Walbaum) reared up to the weight of 380 g in a model recirculated water system contains on average 1.28 g omega-3 polyunsaturated fatty acids per 100 g, whereas its consumption rate is 1–3 g per day for human adults. Selenium content in the meat of the rainbow trout underyearlings fed during 110 days by the preparation Essex (1 mL/kg of feed) has increased up to 20.1 mg/100 g (7.3 mg above the control) that corresponds to 28.7 and 36.6 % of the daily consumption rate of selenium for man and woman, respectively. This raw material can be used for production of ecologically clean and functional food products in cases of selenium scarcity. Besides, survival rate of the underyearlings increased by 11.7 % and their yield by 17.5 %. Prospects are shown of a new direction in innovative biotechnology toward production of functional food in high-tech industrial aquaculture using a purposeful enrichment of fish meat with specified nutrients